A new species of Versicorpus Deschodt, Davis & Scholtz, 2011 (Scarabaeidae: Scarabaeinae: Byrrhidiini) from the Brandberg Mountain, Namibia - Deschodt, Christian M.; Sole, Catherine L. (Zootaxa, 2019)
The recently described dung beetle tribe Byrrhidiini currently comprises seven genera and nineteen species (Davis et al. 2019). During a recent collecting expedition to the Brandberg Mountain [S21.11° E14.69°] in Namibia, a single male specimen, together with various disarticulated body parts of a new species belonging to this tribe were collected. It was found amongst dried hyrax (Procavia capensis) dung pellets between large granite boulders. This new species clearly fits the current definition of the genus Versicorpus Deschodt, Davis & Scholtz, 2011. This raises the number of the constituent species of Versicorpus to three and that for Byrrhidiini to twenty.